Jejak Integrasi Ilmu dan Iman dalam Teknologi Islam: Kontribusi Al-Khwarizmi dan Al-Jazari - Dina, Farha (Maliki Interdisciplinary Journal, 2025)
Modern science and technology are often developed separately from religious values, leading to a gap between science and spirituality. In contrast, the history of Islamic civilization shows that Muslim scholars built their scientific endeavors upon the foundation of tawhid (divine unity). This article aims to explore the integration of science and faith in Islamic technology through the contributions of two major figures: Al-Khwarizmi and Al-Jazari. This study employs a qualitative approach using a library research design and content analysis of relevant primary and secondary sources. The findings reveal that Al-Khwarizmi developed mathematics as an instrument for implementing Islamic law, such as in the calculation of zakat, inheritance, and prayer times. Meanwhile, Al-Jazari designed mechanical technologies that were not only functional but also rich in spiritual and symbolic meaning, such as order and harmony that reflect the principle of tawhid. Based on this analysis, a consistent integrative pattern between scientific and spiritual dimensions is evident in both scholars’ works. This study concludes that the contributions of Al-Khwarizmi and Al-Jazari form a significant foundation for developing an Islamic scientific paradigm that integrates reason, revelation, and ethical values in the advancement of modern science and technology.